Insights into the Causes and Predictability of the 2022/23 California Flooding - Schubert, Siegfried D.; Chang, Yehui; DeAngelis, Anthony M.; Lim, Young-Kwon; Thomas, Natalie; Koster, Randal D.; Bosilovich, Michael G.; Molod, Andrea M.; Collow, Allison; Dezfuli, Amin (AMS, 2024)
In late December of 2022 and the first half of January 2023 an unprecedented series of atmospheric rivers (ARs) produced near record heavy rains and flooding over much of California. Here we employ the NASA GEOS AGCM run in a “replay” mode, together with more idealized simulations with a stationary wave model, to identify the remote forcing regions, mechanisms and underlying predictability of this flooding event. In particular, the study addresses the underlying causes of a persistent positive Pacific/North American (PNA) - like circulation pattern that facilitated the development of the ARs. We show that that pattern developed in late December as a result of vorticity forcing in the North Pacific jet exit region. We further provide evidence that this vorticity forcing was the result of a chain of events initiated in mid-December with the development of a Rossby wave (as a result of forcing linked to the MJO) that propagated from the northern Indian Ocean into the North Pacific. As such, both the initiation of the event and the eventual development of the PNA depended critically on internally-generated Rossby wave forcings, with the North Pacific jet playing a key role. This, combined with contemporaneous SST (La Niña) forcing that produced a circulation response in the AGCM that was essentially opposite to the positive PNA, underscores the fundamental lack of predictability of the event at seasonal time scales. Forecasts produced with the GEOS coupled model suggests that useful skill in predicting the PNA and extreme precipitation over California was in fact limited to lead times shorter than about 3 weeks.